Analysis of the use of declared and classic orthopedic tools in order to diagnosis significant parameters towards to research patient’s group with generalized periodontitis in stabilization phase - Іщенко, П. В.; Борисенко, Анатолій Васильович; Іщенко, Т. М. (Actual Dentistry, 2019)
Relevance. In orthopedic treatment of patients with generalized periodontitis in the stage of stabilization, a significant place is given to the functional restoration of the integrity of the dentition, the return of lost chewing effectiveness and quality of life. It is noted that certain constructions of known tires and implants do not fully satisfy the patient’s dental maxillary system caused by periodontitis. After orthopedic treatment, there is a significant deterioration of the HI, PMA of the oral cavity and bone destruction, tissue inflammation can be traced. Given this, a new system of splinting and new designs of subperiostal implants has been proposed, which is non-invasive for the bone that has been provoked. Aim of the study is to reveal the clinical advantage of the proposed orthopedic structures (tires and dental implants) in patients exposed to generalized periodontitis in the stabilization stage using valuable indicators of HI, PMA, densitometry, CBAD and LDF. Materials and methods. Three groups of patients with 174 patients with generalized periodontitis in the stabilization stage were studied and analyzed. The first group had patients without defects of the dentition who needed splinting. The second group of patients had defects in the dentition, which were leveled by various bridges and splinting. The third group is a group mainly with end defects of the dentition, where it is necessary to use various implant systems. Each group consisted of a study group and a control group. In the study group, the proposed tires and the proposed subperiostal dental implants were used. control group includes wellknown tires and well-known endoosseus implants. Results. It has been shown that the use of new proposed interdental tires and subperiostal implants significantly improves the orthotic treatment of patients with generalized periodontitis at the stage of stabilization of diagnostically valuable indicators of HI, PMA, densitometry, CBAD and LDF in the remote time. Conclusions. Studies in groups of patients for 18 months of research have revealed a priority in working with the periodontal-induced new proposed splinting constructions and the proposed subperiostal implants. The advantage lies in the fact that the proposed tires do not alter the anatomical shape of the dentition, being in the middle of the tooth, and the implants do not require invasion of the bone provoked by periodontitis and have physiological micromobility. Key words: subperiostal implant, splinting, generalized periodontitis in stabilization phase, diagnosis significant parameters.